Determinasi Kepuasan dan Loyalitas Pengguna Jasa Pendidikan pada Kinderfield School Cabang Bekasi Jawa Barat - Sri Lestari; Slamet Heri Winarno (Sekolah Tinggi Ilmu Ekonomi Indonesia (STEI) Jakarta, 2018)
Competition in business services, especially education services show a trend that increasingly tight nowadays. Each school is required to be able to create a level of satisfaction and loyalty for its service users. Similarly, conducted by Kinderfield School branch Bekasi which is one of the providers of education services that always strive for the purpose. This study was conducted to determine the effect of service quality, corporate image and price perception in creating customer satisfaction and loyalty at Kinderfield School Bekasi. In this study using 173 respondents as sample by using method of saturated sampling. This research is a quantitative research using observation method, interview and spreading of questionnaire. The analysis technique used is Structural Equation Modeling (SEM) with Likert scale. Variables used include: quality of service (X1), corporate image (X2), price perception (X3), customer satisfaction (Y1) and customer loyalty (Y2). The results showed that customer satisfaction is influenced by corporate image and price perception of 18.4% while customer loyalty is influenced by price perception and customer satisfaction of 60.5%. This suggests that service quality is not always a decisive factor of customer satisfaction and loyalty.